Adult education under a comparative lens: areas of influence - Holford, John; Milana, Marcella; Rasmussen, Palle (Emerald, 2018)
This chapter outlines key areas of literature and policy that have influenced or affected our research on the comparative study of adult education. Policy influences include the growth of lifelong learning within a neoliberal framing since the 1990s and the rise of ‘evidence-based’ approaches with a narrow reliance on quantitative data. Much of our work has been inspired by the need to critique these trends, adopt broader approaches to lifelong learning and defend the more democratic traditions of adult education. Important areas of theoretical inspiration, many of which interrogate these policy developments, are also outlined. The critical reinterpretation of historical adult education practices is another important area of work and inspiration. In relation to sustainability, we have been influenced particularly by the capabilities approach.